PENGARUH KAPASITAS MESIN DAN JUMLAH PERSEDIAAN BAHAN BAKU TERHADAP VOLUME PRODUKSI - Sutrisno, Niantoro; Faradila, Rizka; Sirait, Edison P. (Jurnal Akuntansi dan Bisnis, 2024)
Background of this research based on  data’s observational at a company relating to capacity, amount of raw material inventory and production volume where the phenomena that occur still need to be optimized. This research uses a quantitative approach and uses primary data as a data source obtained from the results of questionnaires distributed to respondents related to activities in accordance with the specified research variables. The analytical methods used are instrument testing, classical assumption testing, multiple regression analysis, hypothesis testing and coefficient of determination (Adjusted R2). The results of this research show that:1. The machine capacity variable partially has a positive and significant effect on production volume at PT. Gema Graha Saran, Tbk Bekasi Regency.2. The raw material inventory variable partially has a positive and significant effect on production volume at PT. Gema Graha Sarana, Tbk Bekasi Regency.3. The variables of machine capacity and raw material inventory simultaneously have a positive and significant effect on production volume at PT. Gema Graha Sarana, Tbk Bekasi Regency       Keywords :Raw Material Inventory, Machine Capacity, and Production Volume